Analisis Implementasi Inovasi Terbuka : Peran Kerjasama Eksternal terhadap Inovasi Produk dan Kinerja Perusahaan (Studi Empiris pada Usaha Kecil dan Menengah (UKM) Batik di Yogyakarta) - Muhammad Akbar Langlang Buwana; Siti Nursyamsiah (Jurnal Manajemen dan Bisnis Indonesia, 2018)
A dynamic business environment put a high pressure on the companies to improve their innovation capabilities continously. It could be achieved by making a collaboration with external parties to capture their knowledge and technology, and then turning it into innovative products and services that companies provided. The aims of this study is to determine the effectiveness of open innovations implementation in Batik Industry in Yogyakarta on firm performance. It focuses on the analyzing of the company's ability in collaborating innovatively with external parties, such as competitors, government, and research institutions. Small Medium Enterprise (SMEs) of Batik Industry in Yogyakarta is used as the population. The sample is choosed by using convenience simple random sampling method that result in 96 SMEs. Then, the data is analysed through the Partial Least Square (PLS) method using 3 independent variables, inter-company cooperation, companies and government cooperation, and companies and research institutions cooperation that tested on firm performance. Besides, product innovation also used as intervening variable. The findings show that a collaboration between companies and government have a positive effect on product innovation, while firm collaboration with research institutions has no effect on product innovation. The role of product innovation as an intervening variable in this model is significant in mediating the effect of external parties collaboration on firm performance. Further, these findings is expected to contributed on SMEs strategies development in building innovation capabilities, particularly in open innovation implementation that would affect firm performance. Keywords: External Cooperation, Innovation, Performance